Fabrication of high-performance microfluidic SERS substrates by metal-assisted chemical etching of silicon scratches. (1st September 2022) - Peng, Yong; Cui, Licong; Gao, Jian; Jiang, Shulan; Wang, Hongbo; Yu, Bingjun; Qian, Linmao
Abstract: Surface-enhanced Raman spectroscopy (SERS) substrate-based microfluidic systems are applied extensively in diverse fields. For affordable detection and diagnosis, we propose a novel strategy for flexible, low-cost, and rapid fabrication of microfluidic SERS substrates by metal-assisted chemical etching of scratches on a silicon surface. A silicon substrate was spin-coated with polyketone resin (PK), and patterned by scratching with a diamond tip. Notably, defects created by diamond tip scratching on silicon substrate promoted subsequent metal deposition. A micro/nano nested structure was prepared by metal-assisted chemical etching process based on combined effect of scratching and metal catalysis. The PK layer served as a stable mask during metal deposition and etching. The prepared SERS-active detection sites with micro/nano nested structures exhibited substantial enhancement effects and good stability. Taking rhodamine 6G as a probe molecule, the microfluidic SERS substrate exhibited a high detection capability, with nanomolar detection limits (10 −9 M) and high long-term stability (at least 120 days). The micro/nano nested structure exhibited an enhancement factor of 2.725 × 10 5 compared to a gold film deposited on a flat silicon surface. The proposed method is promising for chemical and biological detection applications.